(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
When Yvon Chouinard, the founder of Patagonia, started to forge pitons (a piece of climbing equipment) in 1957, he never planned to become a businessman. All he wanted to do was produce climbing gear for his friends and himself. However, half a century later, his company Patagonia (now worth 3 billion dollars) has become one of the most renowned outdoor brands on the market. It is also known to be one of the most sustainable clothing companies in the world and, as a business, incorporates its core values into all its actions. Altogether, Patagonia evokes the coherent aesthetic image of an organisation that is very much in alignment with its purpose, stakeholders, and the environment. In our paper, we examine this notion of alignment and think of it as a kind of resonance between the organisation, its purpose and its stakeholders – a dynamic process of unfolding, co-creating and being co-created in and for a thriving environment. Using Patagonia’s example, the paper aims to provide practical implications and principles based on theoretical foundations related to organisational capabilities, such as understanding and leveraging future potentials and fostering a mindset of resonance and co-creation. To this end, we draw on recent interdisciplinary findings from future-oriented approaches to innovation, creativity, enactive cognitive science and anthropology, as well as organisational learning and spiritual knowledge management, and place them in the context of the challenges of today’s VUCA world.